Post-exercise energy intake: do the intensity and mode of exercise matter? A systematic review and meta-analysis comparing high-intensity interval with moderate-intensity continuous protocols - Rossi, Priscila Almeida Queiroz [UNESP]; Panissa, Valéria Leme Gonçalves; Silveira, Rodrigo; Takito, Monica Yuri; Lima, Fernanda Santos; Rossi, Fabrício Eduardo; Franchini, Emerson (Springer Nature, 2021)
The present systematic review and meta-analysis aimed to compare the impact of exercise intensity and mode (high-intensity interval exercise-HIIE or sprint interval exercise-SIE versus moderate-intensity continuous exercise-MICE) on post-exercise ad libitum energy intake. The studies were required to have at least two exercise conditions (HIIE or SIE vs MICE). Overall, 642 manuscripts were initially identified and 17 met the eligibility criteria. The random effect meta-analysis did not reveal differences for absolute energy intake (28 pairwise comparisons) between HIIE (p = 0.54; 95% Confidence Interval – CI: −0.14 to 0.26; 22 pairwise comparisons) or SIE (p = 0.08; 95% CI −0.65 to 0.03; 6 pairwise comparisons) versus MICE, neither for relative energy intake (p = 0.97; 95% CI: −0.35 to 0.10 for HIIE; p = 0.28; 95% CI: −1.03 to 0.06 for SIE) with five and one pairwise comparisons, respectively. Subgroup analyses for methods to evaluate ad libitum energy intake, body mass, sex, volume, and timing of exercise were non-significant. Inspecting each study, two pairwise comparisons reported lower post-exercise absolute energy intake in HIIE compared to control (CRTL), and three pairwise comparisons reported lower absolute energy intake after SIE compared to MICE. None pairwise comparison reported differences between protocols (HIIE or SIE versus MICE) for relative energy intake. In conclusion, the meta-analysis did not show differences between protocols for absolute and relative energy intake; five pairwise comparisons from 28 demonstrated lower absolute energy intake in HIIE or SIE compared to CRTL or MICE. Further studies are needed to address the key relevant variables in which exercise intensity and mode may impact energy intake.